ESTUDO FITOQUÍMICO E AVALIAÇÃO ANTITUMORAL DO LÁTEX DE Synadenium grantii Hook. f. (Euphorbiaceae) - Oliveira, Thais Latansio de (2013)
The Synadenium grantii Hook f. species is a plant of the Euphorbiaceae family and is popularly known as cega-olho, leitosinha, janaúba, cola-nota among other names. Its latex has been used traditionally in the region of “Campos Gerais” as "garrafada", obtained from this dilution in water (18 drops into 1 liter). Its medicinal applications are widespread in Brazilian popular culture to cure various types of cancer, among other diseases, such as inflammation and ulcers. However, there are no scientific studies that prove these effects besides little is known about the chemical constitution of the species. The aims of this study was to conduct a phytochemical study of S. grantii latex; evaluate its antitumor activity in vitro against melanoma cell line (B16F10); analyze the changes in the distribution of tumor cells in cell cycle phases and also to evaluate the antitumor activity of latex in vivo and histological changes in animals treated with the popular way to use latex plant. The evaluation phytochemical latex was carried out by chromatographic procedures (column chromatography and thin layer chromatography) and spectroscopic procedures (1H NMR and 13C) from which was obtained the isolation and characterization of a triterpenoid and steroid identified as euphol respectively and citrostadienol. Evaluation of the cytotoxicity was determined by the reduction method of MTT ([3 - (4,5-dimethylthiazol-2-yl) -2,5-diphenyltetrazolium bromide) and by exclusion with Trypan Blue. For the tests in vitro, látex concentrations of 0.012 μg/well to 48.8 mg/well were tested and also two isolated compounds (Euphol and Citrostadienol) at concentrations of 2.5 mg/mL - 250μg/mL. To assess changes in the cell cycle, the cells were analyzed by flow cytometry and histological evaluation was performed by hematoxylin-eosin. The cytotoxic assays demonstrated that the S. grantii latex was able to reduce the growth and viability of the cell lines showing concentration and time dependent effect in both methodologies evaluated. In addition, induced cell cycle arrest in S- G2/M phase. Isolated substances only citrostadienol showed a reduced cytotoxic activity in vitro against B16F10 lineage. In vivo assays demonstrated a reduction of 40% in the size of tumours in mice treated with the popular way to use latex but the histological evaluation of organs analyzed (tumor, lung, liver and lymph nodes) was similar in the treated and untreated animals.